2001
DOI: 10.1016/s1010-7940(01)00945-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of coronary artery bypass grafting procedure in the presence of left ventricular dysfunction and hibernating myocardium

Abstract: CABG procedure in the presence of HM enhances LV recovery of function and has a favourable prognosis. Functional benefit of the left ventricle, however, appears to be time-limited, despite remarkable improvement in patient functional capacity. Advanced preoperative heart failure, minimal perioperative improvement of LVEF, and age account for a poor long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 21 publications
6
37
1
Order By: Relevance
“…In our study, dobutamine stress echocardiography was performed preoperatively in all patients by the same cardiologist, and thallium-201 rest-redistribution scintigraphy was performed in 43 (57%) patients. Both techniques are valuable in the identification of hibernating myocardium and in the prediction of a favorable postoperative outcome [13]. We confirmed in earlier research [9] that the preoperative presence of hibernating myocardium is a predictor of immediate postoperative improvement of left ventricular function in these patients.…”
Section: Assessment Of Hibernating Myocardium and Patient Selectionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our study, dobutamine stress echocardiography was performed preoperatively in all patients by the same cardiologist, and thallium-201 rest-redistribution scintigraphy was performed in 43 (57%) patients. Both techniques are valuable in the identification of hibernating myocardium and in the prediction of a favorable postoperative outcome [13]. We confirmed in earlier research [9] that the preoperative presence of hibernating myocardium is a predictor of immediate postoperative improvement of left ventricular function in these patients.…”
Section: Assessment Of Hibernating Myocardium and Patient Selectionsupporting
confidence: 85%
“…Our finding supports the observation of Lansman and colleagues [21], who stated that the presence of angina predicted a good survival rate and a consistent improvement in left ventricular function. However, other investigators [13] have shown that the presence of angina had no statistically significant predictive value with regard to long-term mortality and the recurrence of heart failure. Dreyfus and colleagues [22] emphasized the importance of using viability tests instead of clinical evaluation as a crucial determinant of patient selection and subsequent postoperative outcome.…”
Section: Predictors Of Late Outcomementioning
confidence: 87%
See 1 more Smart Citation
“…The recent trends in CABG procedure have clearly favoured the use of arterial conduits, not only to perfuse the LAD in normal left ventricular function but also in patients with impaired left ventricular function. 19 Jegaden et al, however, recently reported on potential unfavourable effects of extensive use of arterial grafts as compared to more conventional surgical management (LIMA plus vein grafts) to revascularize patients affected by impaired LV function, documenting increased rate of perioperative complications and no benefit as far as survival was concerned. They found significant increase in post-operative LV function in venous group.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple revascularizations to viable and hibernating myocardium may improve myocardial contractility and cardiac function even though global function is severely impaired. 1) Recent meta-analysis demonstrated that CABG can be performed with acceptable operative mortality and 5-year actuarial survival rates in patients with LVD. 2) Advances in surgical techniques (such as off-pump techniques and arterial grafts), myocardial protection, and postoperative management have contributed to improving outcomes in these high-risk patients.…”
Section: Introductionmentioning
confidence: 99%